1984
DOI: 10.1159/000118857
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Licking and Swallowing in the Drinking Rat

Abstract: Licking behavior of rats appeared to be interrupted periodically for about 20 ms. Behavioral and electrophysiological evidence is presented which indicates that during this period swallowing occurs. The hypothesis was tested that swallowing initiation depends on the volume of water that has accumulated in the oral cavity during drinking. No support for this hypothesis was obtained when the flow rate of water through the drinking tube was manipulated. Alternative hypotheses are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…We corrected the volume of ethanol or water consumed during a session for spillage by subtracting 0.1ml from the final measure, consistent with the amount of liquid that spills during handling of the sipper bottles (personal observation). This calculation resulted in an approximate 4.89 μl consumed per lick, with this volume in good agreement with previous studies demonstrating rats consume liquids in the range of 4–8 μl/lick [44]. This volume/lick multiplied by the number of licks within each hour was then used to determine the grams/kilogram ethanol/hour for each animal.…”
Section: Methodssupporting
confidence: 81%
“…We corrected the volume of ethanol or water consumed during a session for spillage by subtracting 0.1ml from the final measure, consistent with the amount of liquid that spills during handling of the sipper bottles (personal observation). This calculation resulted in an approximate 4.89 μl consumed per lick, with this volume in good agreement with previous studies demonstrating rats consume liquids in the range of 4–8 μl/lick [44]. This volume/lick multiplied by the number of licks within each hour was then used to determine the grams/kilogram ethanol/hour for each animal.…”
Section: Methodssupporting
confidence: 81%
“…This corresponds to a frequency of 6 -7/s, consistent with previous reports of intraorally evoked (17,59) or appetitive licking (10,21,65,69). The mean IGI for QHCl-elicited gaping was 0.30 s. Electrically elicited gaping had a slightly shorter mean IGI, 0.25 s, but this difference only approached significance (T ϭ Ϫ2.302 7 , P ϭ 0.055).…”
Section: Electrical Vs Fluid Stimulationsupporting
confidence: 88%
“…Although there were no significant differences between medial and lateral placements for latency to lick (C), lateral sites displayed longer licking bouts at 24.3 s (D). ited by electrical stimulation had frequency characteristics identical to those in response to intraoral infusions of tastants or water (17,59) and to drinking from a sipper spout (10,21,65,69). QHCl-elicited and electrically evoked gapes were characterized by lower-frequency (3-to 4-Hz), triangular, wide-mouthed movements.…”
Section: Discussionmentioning
confidence: 89%
“…Behavioral studies have shown that rats swallow water during licking without stopping to lick [132]. The water accumulating in the mouth is swallowed every 6–8 licks.…”
Section: The Coordination Of Rhythmic Orofacial Movements: a Proposedmentioning
confidence: 99%